2021
DOI: 10.3389/fonc.2021.626961
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stemness Characteristics Associated With the Immune Microenvironment and Prognosis in Gastric Cancer

Abstract: BackgroundGastric cancer (GC) is a highly heterogeneous disease. In recent years, the prognostic value of the mRNA expression-based stemness index (mRNAsi) across cancers has been reported. We intended to identify stemness index-associated genes (SI-genes) for clinical characteristic, gene mutation status, immune response, and tumor microenvironment evaluation as well as risk stratification and survival prediction.MethodsThe correlations between the mRNAsi and GC prognosis, clinical characteristics, gene mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
(53 reference statements)
1
19
0
Order By: Relevance
“…Moreover, we found that immune score was lower in the high-mRNAsi group than in the low-mRNAsi group for both colon and rectal cancer (Wilcoxon rank sum test, p < 0.001, Figures 2D,G ). Moreover, immune score has been proven lower in the high-mRNAsi group than in the low-mRNAsi group for gastric cancer ( Mao et al, 2021 ). In addition, when comparing the tumor mutational burden (TMB) in groups with different levels of stemness index, we observed the opposite trend, with the level of TMB increasing from the low-mRNAsi group to the high-mRNAsi group (low mRNAsi < high mRNAsi) (Wilcoxon rank sum test, p < 0.001, Figures 2E,H ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we found that immune score was lower in the high-mRNAsi group than in the low-mRNAsi group for both colon and rectal cancer (Wilcoxon rank sum test, p < 0.001, Figures 2D,G ). Moreover, immune score has been proven lower in the high-mRNAsi group than in the low-mRNAsi group for gastric cancer ( Mao et al, 2021 ). In addition, when comparing the tumor mutational burden (TMB) in groups with different levels of stemness index, we observed the opposite trend, with the level of TMB increasing from the low-mRNAsi group to the high-mRNAsi group (low mRNAsi < high mRNAsi) (Wilcoxon rank sum test, p < 0.001, Figures 2E,H ).…”
Section: Resultsmentioning
confidence: 99%
“…The mRNAsi of colon and rectal cancer tissues was significantly higher than that of normal tissues (Wilcoxon rank sum test, p < 0.05, Figures 1A,H), which suggested that the level of stemness is associated with tumor development. The mRNAsi among different stages of colon and rectal cancer did not show significant differences (Mann-Whitney U-test, p < 0.05, Figures 1B,C,I,J), which suggested the mRNAsi may not be closely related to the clinical stage in many tumor types (Bai et al, 2020;Mao et al, 2021;Pei et al, 2020). In our study, the colon and rectal cancer patients were divided into high-mRNAsi and lowmRNAsi groups based on the cutoff value determined by the median mRNAsi index (Figures 1D-G,K-N).…”
Section: Colon and Rectal Cancer Patients Could Be Subtyped Using The Mrnasimentioning
confidence: 93%
“…Numerous studies have been reported to investigate whether tumor immune microenvironment could be affected by stemness features. Mao et al (2021) developed a mRNA expression-based stemness index system based on weighted gene correlation network analysis to reveal that the stemness index indicated a distinct immune spectrum. Alex et al used gene expression-based metrics to evaluate the association of stemness with immune cell infiltration and genomic, transcriptomic, and clinical parameters across 21 solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Here, whether there is an association between the focal adhesion mutation and mRNAsi, our results show that the mRNAsi of patients with mutations is significantly higher than that of patients without mutations (P < 0.0001) (Supplementary Figure 1B). The previous study (Mao et al, 2021) has reported that patients with high mRNAsi have a better prognosis. In terms of prognosis, the results of this study are consistent with them.…”
Section: Focal Adhesion Mutation Type Is Closely Related To Prognosis and Clinicopathological Characteristicsmentioning
confidence: 91%
“…The mRNA expression-based stemness index (mRNAsi) of GC was reported by Malta et al (2018). TMB of GC was extracted according to the method we reported before (Mao et al, 2021). The focal adhesion-related genes (Supplementary…”
Section: Data Acquisition and Processingmentioning
confidence: 99%